Perencanaan Strategis Peningkatan Mutu Pendidikan Melalui Analisis Swot (Studi Kasus SDN Duri Kosambi 01 Jakarta Barat) - Soro, Suharyanto H.; Vindusari, Maria Kleovita Putri; Rosmawati, Rosmawati; Siswanti, Sri (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Improving the quality of education can be done using various methods and approaches. Education units experience shortcomings and weaknesses in implementing quality improvement methods based on the results of analysis and facts that occur in the field. Therefore, appropriate strategic planning is needed by educational units. In other words, strategic planning in primary and secondary education units needs to be improved to realize better quality education. The aim of this research is to discover and describe the importance of strategic planning to improve the quality of school education using SWOT analysis (Strengths, Weaknesses, Opportunities and Threats). This research uses a qualitative method with a case study approach. Research object at SDN Duri Kosambi 01. Data collection methods through interviews, observation and document analysis. The research results show that (1) SWOT analysis of the internal environment has more advantages (Strengths) than disadvantages (Weaknesses); (2) Opportunities are greater than risks in the SWOT analysis of the external environment; (3) Using SWOT analysis in strategic planning can improve the quality of education.